2007
DOI: 10.1091/mbc.e07-03-0263
|View full text |Cite
|
Sign up to set email alerts
|

putzigIs Required for Cell Proliferation and Regulates Notch Activity inDrosophila

Abstract: We have identified the gene putzig (pzg) as a key regulator of cell proliferation and of Notch signaling in Drosophila. pzg encodes a Zn-finger protein that was found earlier within a macromolecular complex, including TATA-binding protein-related factor 2 (TRF2)/DNA replication-related element factor (DREF). This complex is involved in core promoter selection, where DREF functions as a transcriptional activator of replication-related genes. Here, we provide the first in vivo evidence that pzg is required for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
64
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(66 citation statements)
references
References 43 publications
2
64
0
Order By: Relevance
“…Despite the relative simplicity of primary Notch signaling, the presence of a large number of fine-tuning regulators at different levels, from the outside of the cell membrane to the nucleus, dramatically increases the complexity of Notch pathway outputs and its cellular responses, thus controlling a wide range of developmental processes (Neumann and Cohen, 1998;Acar et al, 2008;Hautbergue et al, 2009;Kim et al, 2009;Xie et al, 2012). At the nuclear level, recent findings suggest that chromatin-associated regulatory mechanisms are important for proper Notch target gene expression (Bray et al, 2005;Kugler and Nagel, 2007;Moshkin et al, 2009;Duan et al, 2011;Mulligan et al, 2011;Domanitskaya and Schüpbach, 2012;Endo et al, 2012). Transcriptional silencing complexes have been identified by proteomic methods in the absence of Notch activation (Moshkin et al, 2009;Mulligan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relative simplicity of primary Notch signaling, the presence of a large number of fine-tuning regulators at different levels, from the outside of the cell membrane to the nucleus, dramatically increases the complexity of Notch pathway outputs and its cellular responses, thus controlling a wide range of developmental processes (Neumann and Cohen, 1998;Acar et al, 2008;Hautbergue et al, 2009;Kim et al, 2009;Xie et al, 2012). At the nuclear level, recent findings suggest that chromatin-associated regulatory mechanisms are important for proper Notch target gene expression (Bray et al, 2005;Kugler and Nagel, 2007;Moshkin et al, 2009;Duan et al, 2011;Mulligan et al, 2011;Domanitskaya and Schüpbach, 2012;Endo et al, 2012). Transcriptional silencing complexes have been identified by proteomic methods in the absence of Notch activation (Moshkin et al, 2009;Mulligan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous Notch target genes have been identified in different tissues or organs during different developmental stages, how the Su(H)-NICD-Mam ternary complex regulates their expression is largely unclear. Recent findings in different systems have suggested that chromatin-associated epigeneticallyregulatory mechanisms are very important for proper expression of Notch target genes (Bray et al, 2005;Domanitskaya and Schüpbach, 2012;Endo et al, 2011;Kugler and Nagel, 2007;Mulligan et al, 2011;Yu et al, 2013;Zeng et al, 2013). In flies, histone chaperones Asf1 and Nap1 are differentially associated with LID-associated factor (LAF) and RPD3-LID-associated factor (RLAF) silencing complexes to mediate epigenetic silencing at the Notch target Enhancer of Split [E(spl)] cluster (Moshkin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It encodes a zinc finger protein with a molecular weight of about 160 kDa (Eggert et al 2004;Kugler and Nagel 2007). Pzg was identified as p160, being an integral component of the TATA-binding protein-related factor 2 (TRF2)/ DNA replication-related element binding factor (DREF) multiprotein complex (Hochheimer et al 2002).…”
mentioning
confidence: 99%
“…The downregulation of pzg gene activity by RNA interference (pzg-RNAi) revealed the fact that Pzg is essential for the function of the TRF2/DREF complex, which regulates cell cycling and growth during Drosophila development (Kugler and Nagel 2007). The ubiquitous induction of pzg-RNAi is associated with a developmental delay and leads to loss of tissue due to reduced proliferation (Kugler and Nagel 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation